2010
DOI: 10.1055/s-0030-1258300
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Three-Component Synthesis of 3-(5-Alkyl/aryl-1,3,4-oxadiazol-2-yl)-3-hydroxy-1,3-dihydro-2H-indol-2-ones

Abstract: An efficient three-component synthesis of 3-(1,3,4-oxadiazol-2-yl)-3-hydroxy-1,3-dihydro-2H-indol-2-ones is described. A mixture of N-isocyaniminotriphenylphosphorane, an isatin, and a carboxylic acid undergoes a 1:1:1 addition reaction under mild conditions to afford the title compounds in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…As shown in Scheme A, much emphasis has been put on the investigation of the oxo-component reactivity. The reaction works well with aliphatic and aromatic aldehydes but only with highly reactive ketones. ,, As expected, ketones are less likely to interact with the sterically congested isonitrile partner and to react properly, they must be highly strained (e.g., cyclobutanone) or bear electron-deficient substituents (e.g., α-halo-ketones, , isatine, acenaphthoquinone, α-acyloxy propanones, , and 1,2-diketones). ,, The preferred solvents are DCM, chloroform, and acetonitrile, although water has been employed with good results in the pursuit of greener procedures. ,, The mild conditions and general applicability of this reaction recently led to medicinal applications, such as the screening of oxadiazole libraries, to seek antibacterial compounds . Thus, it was found that some oxadiazole derivatives containing a pyridine ring were fairly active against Staphylococcus aureus and Staphylococcus epidermidis .…”
Section: Oxadiazole Synthesis By Three-component Reactionmentioning
confidence: 61%
See 2 more Smart Citations
“…As shown in Scheme A, much emphasis has been put on the investigation of the oxo-component reactivity. The reaction works well with aliphatic and aromatic aldehydes but only with highly reactive ketones. ,, As expected, ketones are less likely to interact with the sterically congested isonitrile partner and to react properly, they must be highly strained (e.g., cyclobutanone) or bear electron-deficient substituents (e.g., α-halo-ketones, , isatine, acenaphthoquinone, α-acyloxy propanones, , and 1,2-diketones). ,, The preferred solvents are DCM, chloroform, and acetonitrile, although water has been employed with good results in the pursuit of greener procedures. ,, The mild conditions and general applicability of this reaction recently led to medicinal applications, such as the screening of oxadiazole libraries, to seek antibacterial compounds . Thus, it was found that some oxadiazole derivatives containing a pyridine ring were fairly active against Staphylococcus aureus and Staphylococcus epidermidis .…”
Section: Oxadiazole Synthesis By Three-component Reactionmentioning
confidence: 61%
“…The reaction works well with aliphatic and aromatic aldehydes but only with highly reactive ketones. 69,70,74−77 As expected, ketones are less likely to interact with the sterically congested isonitrile partner and to react properly, they must be highly strained (e.g., cyclobutanone) 78 or bear electron-deficient substituents (e.g., α-halo-ketones, 70,79 isatine, 73 acenaphthoquinone, 80−82 α-acyloxy propanones, 83,84 and 1,2-diketones). 71,72,85−87 The preferred solvents are DCM, chloroform, and acetonitrile, although water has been employed with good results in the pursuit of greener procedures.…”
Section: ■ Niitp In Oxadiazole Chemistry: From Bimolecular To Four-co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, they developed a 1:1:1 addition reaction of NIITP 1 , isatins 47 and acarboxylic acids 48 for the synthesis of 3‐(1,3,4‐oxadiazol‐2‐yl)‐3‐hydroxy‐1,3‐dihydro‐2 H ‐indol‐2‐ones 49 (Scheme ) …”
Section: Multicomponent Reactionsmentioning
confidence: 99%
“…102 The process included addition of isonitrile carbon atom to isatin and subsequent aza-Wittig reaction (Scheme 42).…”
Section: Scheme 40mentioning
confidence: 99%